The Effectiveness Of Blended Learning Strategy On Students’ Writing Competency Of The Tenth Grade Students - Gede Juni Arta; Ni Made Ratminingsih; Made Hery Santosa (Jurnal Pendidikan Indonesia, 2019)
This research aimed at investigating whether or not there was a significant difference on writing competency of the tenth grade students at SMA Negeri 1 Singaraja. This research was experimental research with Pre-test and Post-test Only Control Group Design and used cluster random sampling technique to determine the samples. There were two classes chosen as samples in this study. The two groups were given treatments to obtain the required data. The experimental group was taught by using Blended Learning Strategy and the control group was taught by using conventional technique. The obtained data were analyzed descriptively and inferentially. The mean score of experimental group (81.10) was higher than the mean score of control group (78.83). Moreover, the result of inferential analysis showed that there was a significant difference on students’ writing competency between the students who were taught by using Blended Learning Strategy and those who were taught by conventional technique (Sig.(2-tailed) = 0.022, p < 0.05). The alternative hypothesis is accepted in which the students who are taught by using Blended Learning Strategy achieves better than those who are taught by using conventional technique.